2011
DOI: 10.1007/s10577-011-9249-9
|View full text |Cite
|
Sign up to set email alerts
|

Specific positioning of the casein gene cluster in active nuclear domains in luminal mammary epithelial cells

Abstract: The nuclear organization of mammary epithelial cells has been shown to be sensitive to the three-dimensional microenvironment in several models of cultured cells. However, the relationships between the expression and position of genes have not often been explored in animal tissues. We therefore studied the localization of milk protein genes in the nuclei of luminal mammary epithelial cells during lactation as well as in two non-expressing cells, i.e., hepatocytes and the less differentiated embryonic fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…At the other extreme, one copy of demethylated DNA is present in every cell and both copies are demethylated in 20% of cells. This latter hypothesis, under which all cells are expected to express one copy of the CSN gene, fits better with our histological findings (Figure 3) and in situ hybridization results, which revealed an accumulation of CSN transcripts in a large proportion of luminal epithelial cells during lactation [47].…”
Section: Discussionsupporting
confidence: 91%
“…At the other extreme, one copy of demethylated DNA is present in every cell and both copies are demethylated in 20% of cells. This latter hypothesis, under which all cells are expected to express one copy of the CSN gene, fits better with our histological findings (Figure 3) and in situ hybridization results, which revealed an accumulation of CSN transcripts in a large proportion of luminal epithelial cells during lactation [47].…”
Section: Discussionsupporting
confidence: 91%
“…Here localization was stated to be predictive for the developmental state of the T cell (Merkenschlager et al, 2004). Localization of inactive genes to the nuclear periphery was also found for the human CFTR locus (Zink et al, 2004; Ballester et al, 2008) and the casein cluster in mammary glands (Kress et al, 2011). …”
Section: Gene Positioning In the Cell Nucleusmentioning
confidence: 74%
“…At the end of lactation, the CpG sites are highly methylated again until the next lactation. Kress et al (2011) reported another regulation mechanism. These authors showed an association between the localization of milk protein genes in the nuclei of luminal mammary epithelial cells and their expression.…”
Section: Gene Expression At Lactationmentioning
confidence: 99%